Government role in influencing creative economy for community purchasing power - Dedeh Maryani; Rossy Lambelanova (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This research was conducted to find out whether the West Java provincial government has implemented the development of creative economy by looking at the form of policy and budget support in APBD and the problem. The results show, West Java Provincial Government has made regional regulations and creative economic blueprints. It is suggested to be more committed to facilitate the marketing of results, facilitate business actor access to banking, protection of intellectual property rights, and enhancement of cooperation between provinces and districts/municipalities for the sustainability of necessary raw materials.